Forensic genetic research on sudden unexpected death in an infant (SUDI) at Salt River Mortuary: experiences an perceptions of parents - Louw, Susan (Department of Pathology, 2019)
The unexpected and sudden death of an infant (SUDI) is a traumatic event. SUDI is defined as all deaths occurring suddenly and unexpectedly in infants under the age of one year. Molecular autopsy is used to determine the potential genetic contribution to SUDI and may lead to screening and interventions of at-risk family members. However, the potential of this may only be realised if the family members are willing to engage in the follow-up process. Next-of-kin experiences of participating in molecular autopsy research are unknown, and not previously done in South Africa. This study explored the experiences and perceptions of bereaved next-of-kin participating in forensic genetic research on SUDI at Salt River Mortuary, Cape Town. Methods Eleven participants, including the mothers and other family members for six SUDI cases participated in the study. These participants were recruited from a larger forensic molecular autopsy study conducted at the University of Cape Town. In order to explore the experiences and perceptions of next-of-kin, a qualitative approach was used and semi structured interviews were conducted. The interviews, transcribed verbatim, were analysed through thematic analysis. The perspective from the main researcher in the larger forensic molecular autopsy study was included to holistically explore the setting in which the genetics research took place. Results Four major themes were identified, namely (i) old wounds, (ii) my booboo, (iii) the sudden death and (iv) afterthought. Their main reasons for participating in the research were to find answers and to be of value in future cases of SUDI. Grief seemed to play a significant role in their understanding and engagement with regards to their research participation. Conclusion This study found that the grief and loss of at the time of obtaining consent may play a significant role in understanding and willingness for further engagement with molecular autopsy results. Understanding has previously been implicated in the willingness to engage with genetics results, however, it has not been explored in a mortuary setting. The understanding of genetics research is critical for further engagement that may have implications for the screening of other family members and future offspring. These findings may allow researchers to better engage with participants in genetics research on sensitive topics, including SUDI.